10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Biomedical waste (BMW) management is a crucial aspect of both human and veterinary healthcare to prevent environmental contamination and transmission of infectious diseases. Veterinary BMW, although often overlooked, comprises hazardous materials such as infectious waste, sharps, pharmaceuticals, chemicals, radioactive substances, and pathological remains. Despite its significant contribution to hazardous waste, veterinary BMW often lacks sufficient regulatory focus and compliance. Various countries have implemented regulatory frameworks, including India's Bio-Medical Waste Management Rules (2016), U.S. regulations by agencies like the Environmental Protection Agency, Occupational Safety and Health Administration, etc., and similar policies in the United Kingdom and South Africa. Common disposal methods include incineration, autoclaving, chemical treatment, and land burial, each with its advantages and environmental concerns. However, challenges such as low awareness, inadequate infrastructure, and poor regulatory enforcement hinder effective BMW management. Strengthening compliance, enhancing infrastructure, and adopting innovative waste management strategies are essential to minimize environmental and public health risks. This review aims to explore the nature, regulatory frameworks, challenges, and sustainable management strategies for veterinary BMW to reduce its deleterious impacts on the environment and health.